The explosion resistance analysis of the safety evacuation device. Issue 1 (February 2020) - Wang, Yong; Feng, Xuezhi; Cui, Lizhuang; Sun, Gengyu; Wang, Yongyan; Jing, Xiumin
Abstract: The explosion resistance is one of the main functions of the safe evacuation device, and the explosion resistance of the safety evacuation device is mainly determined by the safe evacuation cabin, and therefore it requires the building structure to have sufficient strength and stiffness to resist the blast wave application to the cabin. In this paper, a new model of the similar triangular cabin structure is established. The explosion resistance impact analysis of the similar triangular cabin structure is carried out by AUTODYNA and ABAQUS software. The similar triangular cabin structure is placed in the simulated residential building, and the pressure cloud in the room during the explosion and the change of the pressure at each time in the single room can be obtained by TNT explosion test simulation. The pressure curve is used to analyze explosion resistance of the safe evacuation device, and the stress and deformation of the new cabin structure can be obtained. At the same time, the stress concentration are located at the corners of the interior of the cabin and the maximum deformation is located on the front and back walls of the pod which can meets the safety evacuation shock resistance.